2021
DOI: 10.1111/pedi.13259
|View full text |Cite
|
Sign up to set email alerts
|

Tubular injury in diabetic ketoacidosis: Results from the diabetic kidney alarm study

Abstract: Objective Glomerular injury is a recognized complication of diabetic ketoacidosis (DKA), yet the tubular lesions are poorly understood. The aim of this prospective study was to evaluate the presence and reversibility of tubular injury during DKA in children with type 1 diabetes (T1D). Research Design and Methods Blood and urine samples were collected from 40 children with DKA (52% boys, mean age 11 ± 4 years, venous pH 7.2 ± 0.1, glucose 451 ± 163 mg/dL) at three timepoints: 0–8 and 12–24 h after starting insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
7
0
4
Order By: Relevance
“…This implies that these cases are likely to have also developed intrinsic tubular injury, a finding confirmed by several recent studies in children in DKA. 3,19,20 There are few if any studies in the paediatric literature to compare rates of AKI in common paediatric conditions, such as gastroenteritis. The 3 most common causes of hospital acquired AKI are renal perfusion insufficiency, nephrotoxic drugs and contrast agents, two of these are at least potentially avoidable and not seen…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that these cases are likely to have also developed intrinsic tubular injury, a finding confirmed by several recent studies in children in DKA. 3,19,20 There are few if any studies in the paediatric literature to compare rates of AKI in common paediatric conditions, such as gastroenteritis. The 3 most common causes of hospital acquired AKI are renal perfusion insufficiency, nephrotoxic drugs and contrast agents, two of these are at least potentially avoidable and not seen…”
Section: Discussionmentioning
confidence: 99%
“…This implies that these cases are likely to have also developed intrinsic tubular injury, a finding confirmed by several recent studies in children in DKA. 3 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…al reported that DKA is characterized by markers of reversible tubular injury and that the degree of injury is associated with elevated copeptin and serum uric acid (SUA) levels in children with T1DM [3]. In fact, during the onset of T1DM, high levels of copeptin and SUA are associated with the presence of tubular injury markers, such as neutrophil gelatin-associated lipocalin (NGAL), kidney injury molecule 1 (KIM-1), chitinase 3-like 1 (YKL-40), interleukin 18 (IL-18), and monocyte chemoattractant protein-1 (MCP-1) [3]. Aminoaciduria can also be considered a marker of tubular dysfunction, since an increased excretion of amino acids has been reported during DKA [27][28][29].…”
Section: Prevalence and Risk Factors For Tubular Damage In Children A...mentioning
confidence: 99%
“…A delayed therapeutic intervention may lead to the persistence of glomerular vasoconstriction, which may result in an acute tubular necrosis (described in about 30% of patients with T1DM onset [ 1 ]), thus shifting AKI from functional to intrinsic [ 15 , 16 ]. For this reason, there has been a recent focus on the investigation of early tubular AKI biomarkers, in order to diagnose functional AKI in a timely manner, and to hopefully prevent the evolution to intrinsic AKI [ 3 , 17 ].…”
Section: Acute Settingmentioning
confidence: 99%
See 1 more Smart Citation